Event of signature : Jacques Derrida and repeating the unrepeatable - Fisěrová, Michaela (SUNY Press, 2022)
"In dialogue with Derrida, formulates a new philosophical problem - a complex aporia that underlines the topic of the handwritten as a sign of legal identification" -- Provided by publisher.
Keywords: Signatures (Writing) -- Philosophy.; Signature (Law) -- Philosophy.; Signatures -- Philosophie.; Signature (Droit) -- Philosophie.; PHILOSOPHY / Movements / Deconstruction.; Electronic books.